ANALISIS PENGARUH PENDAPATAN ASLI DESA, DANA DESA, DAN ALOKASI DANA DESA TERHADAP BELANJA DESA : FENOMENA FLY PAPER EFFECT - Ade Sabila; Afrah Junita; Agustina Nurul Fajriah (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This study aims to analyze the influence of Village Original Income (PADes), Village Funds, and Allocation of Village Funds on village expenditure, as well as to identify the existence of the flypaper effect in Karang Baru District, Aceh Tamiang Regency. The focus of this study is directed at three villages Simpang Empat, Paya Awe, and Kebun Tanah Terban which were designated as independent villages by the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration (Kemendes PDTT) in 2022. These villages were selected as samples due to their notable PADes potential. The population in this study includes all villages in Karang Baru District, while the sample was determined purposively, consisting of three villages with available Village Original Income data.This study uses a quantitative approach with panel data regression analysis, which combines time series and cross-sectional data. The data were obtained from the Village Budget Realization Reports and analyzed using EViews 10 software.The results of this study indicate that Village Original Income has a negative and insignificant effect on village expenditure, Village Funds also have a negative and insignificant effect on village expenditure, while the Allocation of Village Funds has a positive and significant effect on village expenditure. Additionally, the flypaper effect is present in the region. The limitations of this study lie in its limited geographic scope and sample size, covering only three villages over a six-year period. Furthermore, this study only considers financial variables and does not take into account non-financial factors such as the capacity of village officials or community participation. Therefore, it is recommended that future researchers expand the scope of their study areas.